2011
DOI: 10.1080/09670874.2011.622085
|View full text |Cite
|
Sign up to set email alerts
|

Response of two catchweed bedstraw (Galium aparine) populations to post-emergence herbicides in winter wheat

Abstract: Catchweed bedstraw causes severe problems in winter wheat and other winter sown crops. Field experiments were conducted from 2005 to 2008 in wheat fields in Samsun, Turkey, to determine: (1) the response of catchweed bedstraw to chlorsulfuron, tribenuron-methyl plus thifensulfuronmethyl, dicamba plus triasulfuron and mesosulfuron-methyl plus iodosulfuron-methyl-sodium; and (2) possible resistance or tolerance to these herbicides. The herbicides were applied at the 2-4, 4-6, and 6-8 true leaf stages of biomass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The first case of ALS-inhibitor-resistant redroot pigweed was reported in Ontario in 1997. This population was characterized by high-level resistance to imazethapyr and high-level cross-resistance to thifensulfuron (Ferguson et al 2001;Mennan et al 2011). Poska (2018) reported that redroot pigweed has recently become one of the most important weeds of wheat fields in Russia.…”
Section: Introductionmentioning
confidence: 99%
“…The first case of ALS-inhibitor-resistant redroot pigweed was reported in Ontario in 1997. This population was characterized by high-level resistance to imazethapyr and high-level cross-resistance to thifensulfuron (Ferguson et al 2001;Mennan et al 2011). Poska (2018) reported that redroot pigweed has recently become one of the most important weeds of wheat fields in Russia.…”
Section: Introductionmentioning
confidence: 99%
“…Cleavers is a problematic broadleaved weed in winter crops in Eurasia and North America(Defelice 2002;Mennan & Zandstra 2005;Johnson et al 2018;Zargar et al 2020). This weed is highly adapted to the environment due to its inherent characteristics such as flexibility in the timing of seed germination, variable growth forms, multiple annual lifecycles, freezing tolerance, high dispersal ability and high genetic diversity(Hubner et al 2003;Mennan et al 2011). It is an annual or perennial seminiferous plant, hibernating, climbing, rough to the touch and sticky, which causes direct damage to barley production through the consumption of water and nutrients, but also indirect damage because it makes harvesting difficult and is a host plant for nematodes, insects and pathogens(Ştef et al 2020).…”
mentioning
confidence: 99%